Urgensi Program Bimbingan Konseling di SLTA - Siregar, Ehdatul Puadi; F, Firman; N, Neviyarni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The preparation of the BK program is not an easy thing. The preparation of the BK program must be carried out in a systematic way that is planned, implemented, and evaluated. This BK program is the responsibility of a counselor to carry out his work professionally at a school level. For this reason, in this study, we will discuss how to prepare the BK program at the high school level. The research method used is to be able to answer existing problems by conducting a literature study or literature review by collecting data from scientific works, both books and other scientific works. While the results of the study indicate that the BK program is prepared by each supervising teacher which is an integral part of the entire school program. This program activity contains the elements contained in various provisions regarding the implementation of guidance and counseling and is oriented towards achieving the goals of guidance and counseling activities in schools, in Permendikbud No. 111 of 2014 concerning Guidance and Counseling in Basic Education and Secondary Education Article 8 paragraph 2 explains that the management mechanism as referred to in paragraph (1) letter a is the steps in the management of the Guidance and Counseling program in the education unit which includes steps: needs analysis, planning, implementing, evaluating, reporting, and following up on program development.